Lutherans in Public—Four Lively Options - Benne, Robert (Dialog, 2006)
The basic question regarding faith and the public square is not whether religion should become public. Rather, we should ask: how ought religion to become public? This article reviews four models: (1) the ethics of character, according to which ethically formed individuals exert indirect and unintentional influence on the public square; (2) the ethics of conscience with its indirect and intentional influence: (3) the church as social conscience with direct and intentional influence; and (4) the church with power exerting direct and intentional action. Generally, it is best for Lutherans to let direct action be carried on by the laity according to the first two models; yet, when rare yet extraordinary circumstances call for it, the church as an institution may resort to models three and four and take direct action.